Study Pustaka Pemilihan Skincare Berdasarkan Komposisi Sesuai Dengan Permasalahan Kulit Wajah - Eny Widhia Agustin; Mia Hafizah Tumangger; Axcel Martsanda Pertiwi; Ivana Alicea Hanindita; Mica Corneliah; Aida Maulina; Lucky Amelia Putri; Wahyu Widaningsih (An-Najat, 2024)
The development of cosmetics today varies because cosmetics are a necessity in today's life, because cosmetics are a necessity and lifestyle for women and men of all ages. The purpose of this study is to understand skincare based on the composition that suits skin problems. This study uses a quantitative research method based on literature studies. This study identifies various facial skin care cosmetics. The results of this study discuss the types of facial skin care cosmetics which show that the selection of cosmetic products must be adjusted to the type of skin to prevent negative effects. This study emphasizes that a deep understanding of cosmetic care can improve individual health and self-confidence